Pengaruh Dan Hubungan Karakteristik Petani Terhadap Penggunaan Lahan Sawah Dengan Sistem Pergiliran Komoditi Di Desa Yosowinangun Kecamatan Belitang Madang Raya Kabupaten Oku Timur - Muridin (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2021)
This research was conducted in June–July 2020, with the aim of knowing the magnitude of the increase in income and production cost efficiency with the existence of commodity rotation farming in Yosowinangun Village and to determine the effect and relationship of farmer characteristics on commodity rotational farming income in Yosowinangun Village. The method used is a survey method centered on Yosowinangun Village, the population of which is mostly lowland rice farmers who also operate rotational farming of rice and carp commodities. Furthermore, the sampling method used in this study is using the simple random sampling method. The number of samples taken in this study were 14 samples from 20 farmer populations who were engaged in rotational farming of rice and carp commodities. The results showed that the increase in income obtained by farmers with the use of paddy fields with a rice and carp commodity rotation system was Rp. 1,645,001,-/Ha/production, while the efficiency of the use of production costs shows an R/C ratio value of 1.99, based on the criteria that the R/C Ratio > 1 means that the use of production costs in the commodity rotation system farming is efficient. Furthermore, there is a significant and strong relationship between the dependent variable and the income of the rice and carp commodity rotation system farming with a confidence level of 95%, with a correlation coefficient (R = 0.999), with an F-test value (Fcount = 545.516 > Ftable = 3 ,63).